Catalyst deactivation study of the esterification of dilute acrylic acid with different concentration catalyzed by ion exchange resin - Siti Nazriah, Hamdan (2015)
Acid-catalysed esterification of acrylic acid with 2-ethylhexanol is the principal method for the manufacture of 2-ethylhexyl acrylate. 2-ethylhexyl acrylate is a clear, water-white liquid with a sweet odor and is readily miscible with most organic solvents, but has negligible solubility in water. In chemical industry, 2-ethylhexyl acrylate is primarily used as a reactive building block to produce polymer coating, adhesives and sealants and it can be polymerized itself. In addition, improving the water resistance, weather ability and sunlight resistance of final product can be made in presence of acrylic acid. Industrial waste water generally can be described as the water or liquid carries waste from industrial or commercial processes. The spent water (wastewater) may contain a large variety of organic compound such as acrylic acid, formaldehyde, acetic acid and more but acrylic acid dominate the amount in polymer industrial wastewater that could harm the aquatic organisms. Currently, incineration treatment method is neither environmental friendly and nor economical. So, reactive distillation in esterification process has potential to recover the acrylic acid in the industrial waste water. In this study, the esterification of dilute acrylic acid with 2-ethyl hexanol that catalyzed by ion exchange resin have been carried out. The objective of the present study was to investigate the deactivation of Amberlyst 15 in the esterification of dilute acrylic acid. Homogeneous catalyst have some limitations such as catalyst recovery problem, disposal of toxic wastes formed during reactions, separation of the products, and loss of catalysts that can cause the solid acid catalyst will be choosen in this study. The esterification process have been conducted in presence of Amberlyst 15 as a catalyst and Phenothiazine as polymerization inhibitor under certain conditions. The range of water content in the dilute acrylic acid have been varied and as well as the presence of inhibitor. The catalyst activiy have been characterized to examine the morphology for fresh and used catalyst after the reaction. Another testing was to determine the catalyst compositions, to check the functional group of catalyst and to determine the measurement for its surface area. From the result, catalyst deactivation happened as increase in water content for diluted AA in the reaction mixture. The present study show that more water content needed to dilute AA solution and more polymerization inhibitor to prevent the polyacrylic acid formation in the reactions.